Photobiomodulation of acute pain syndrome after septoplasty - I. V. Kastyro; Yu. S. Romanko; G. M. Muradov; V. I. Popadyuk; I. K. Kalmykov; M. G. Kostyaeva; Yu. Sh. Gushchina; S. G. Dragunova (Biomedical Photonics, 2021)
The paper evaluates the effectiveness of the use of therapeutic laser exposure (photobiomodulation therapy – PBMT) to minimize acute pain in the early postoperative period in patients after septoplasty. The study included two groups of patients. Patients of the first group (31 patients) underwent septoplasty with standard management in the postoperative period. Patients of the second group (31 patients) also underwent septoplasty, and then added PBMT to the standard measures of the postoperative period at 3, 6 and 24 h after septoplasty (λ = 0.890 μm, P = 10 W, 2 min) and then intranasally 48 h after septoplasty (λ = 0.630 μm, P = 8 W, 2 min). In patients of both groups, heart rate variability and pain were assessed using a visual analog scale within 48 hours after septoplasty. In patients of the second group, after the use of PBMT, the indicators of heart rate variability had a significantly lower total power, compared with patients of the first group. So, after PBMT, the ultra-low-frequency component of the spectral analysis of heart rate variability in the first group was 18580 ± 2067 ms2, which is significantly higher than in the second group (8086 ± 3003 ms2) (p <0.001). The low-frequency component of heart rate variability was also significantly higher in the first group (1871 ± 405 ms2) compared to the second (1095 ± 190 ms2) (p <0.005), which indicates an increase in the tension of the sympathetic part of the autonomic nervous system in the group without the use of PBMT. In the first 3 hours after surgery, the severity of pain between the groups did not differ significantly (p = 0.07). In the period from 6 to 24 hours after surgery, patients who did not undergo PBMT experienced significantly higher pain than patients with PBMT (p <0.001). Thus, in our study, the group of patients with PBMT showed better results in pain and heart rate variability compared to the classical rehabilitation of patients after septoplasty.